2021
DOI: 10.3390/ijerph18178967
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Have Home E-Monitoring of Pulmonary Function in Our Patients with Duchenne Muscular Dystrophy in the COVID-19 Pandemic?—A One Center Pilot Study

Abstract: Background: Duchenne muscular dystrophy (DMD) is the most common, progressive, irreversible muscular dystrophy. Pulmonary function is crucial for duration of life in this disease. Currently, the European Respiratory Society is focused on digital health, seeking innovations that will be realistic for digital respiratory medicine to support professionals and patients during the COVID-19 pandemic. Aims: The aim of this study was to investigate whether it is possible to monitor pulmonary function at home using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In our previous study, we showed that it is possible to make assessments of pulmonary function at home in patients with DMD [30]. The present study showed that lung monitoring in patients with neuromuscular diseases is not only possible but participants also benefit from using home spirometry electronic devices.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In our previous study, we showed that it is possible to make assessments of pulmonary function at home in patients with DMD [30]. The present study showed that lung monitoring in patients with neuromuscular diseases is not only possible but participants also benefit from using home spirometry electronic devices.…”
Section: Discussionmentioning
confidence: 60%
“…This prospective, control-case, open-label study was conducted from June 2021 to October 2021 as the third part of the project: "E-monitoring of the pulmonary function in patients with Duchenne muscular dystrophy undergoing respiratory rehabilitation at home"; details of the other parts were described elsewhere [30].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Saudi Arabia, Bamaga et al advised DMD patients to proceed with virtual clinic visits, if possible, to avoid unnecessary contact with other patients who are probably infected [ 20 ]. In our previous study, we presented the possibilities and benefits of home e-monitoring of the pulmonary function in DMD patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%